1999
DOI: 10.1103/physrevb.59.10877
|View full text |Cite
|
Sign up to set email alerts
|

Bulk changes in semiconductors using scanning probe microscopy:  nm-size fabricated structures

Abstract: Hemispherical p/n/p transistor structures ranging from 100 m down to 0.05 m in diameter are fabricated in CuInSe 2 , by application of a high electric field between a conducting diamond tip of an atomic force microscope and a CuInSe 2 crystal. This leads to electromigration of Cu ions in the bulk of the material. The results of this thermally assisted process are the transistor structures. These are characterized by scanning spreading resistance microscopy. For large devices these results are compared and foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Atomic resolution images of the c(10ϫ2) and (111)-(1 ϫ1) structures are shown in Figs. 16 Figure 2͑d͒ shows an atomic resolution image of the pit created in Fig. These findings are consistent with previous STM studies of this system.…”
supporting
confidence: 89%
“…Atomic resolution images of the c(10ϫ2) and (111)-(1 ϫ1) structures are shown in Figs. 16 Figure 2͑d͒ shows an atomic resolution image of the pit created in Fig. These findings are consistent with previous STM studies of this system.…”
supporting
confidence: 89%
“…It is interesting to find out the factors that dominate wire splitting. It was reported that the tip-to-substrate Joule heating current above 1 μA in C-AFM may result in a temperature increase of 100−500 °C based on the heat flow equation, , Δ T = 0.5 P o /π KR where P o is the average power dissipated around the contact, K is the thermal conductivity, and R is the spherical contact radius. Assuming that all of the power P dissipated around the contact, and using the values of R from a few nanometers (for surface protrusions) to 20 nm (for smooth surface; typical tip radius), and K = 130 W/(m·K) for GaN in our case, we obtained Δ T ≪ 1 °C in our case.…”
Section: Resultsmentioning
confidence: 99%
“…Under specific circumstances Cu-transport can be used to change the semiconductor type. In this way p-n homojunctions or nano-scaled transistors are created in chalcopyrites [14][15][16][17][18][19][20]. Furthermore, it has been shown that Cu(In,Ga)Se 2 -based solar cells also recover after a decrease in efficiency caused by electron or proton irradiation [21][22][23].…”
Section: Introductionmentioning
confidence: 95%